An Artificial Imine Reductase based on the Ribonuclease S Scaffold. Issue 3 (3rd February 2014) - Genz, Maika; Köhler, Valentin; Krauss, Michel; Singer, David; Hoffmann, Ralf; Ward, Thomas R.; Sträter, Norbert
Abstract Dative anchoring of a piano‐stool complex within ribonuclease S resulted in an artificial imine reductase. The catalytic performance was modulated upon variation of the coordinating amino acid residues in the S‐peptide. Binding of Cp*Ir (Cp*=C5Me5) to the native active site resulted in good conversions and moderate enantiomeric excess values for the synthesis of salsolidine.